Penerapan metode bercerita dalam pembelajaran Bahasa Indonesia untuk meningkatkan keterampilan Berbicara siswa kelas 1 SDN 4 Masbagik Utara: The Implementation of Storytelling Method in Indonesian Language Learning to Improve Speaking Skills of Grade 1 Students at SDN 4 Masbagik Utara - Pransisca, Made Ayu; Alim, Abdul (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to improve the speaking skills of 1B grade students at SDN 4 Masbagik Utara through the implementation of a participatory storytellingmethod. In this approach, the teacher acts as a facilitator who guides andprovides opportunities for students to actively engage in the storytellingprocess. The learning activities are carried out through several stages: introduction of a short story, group storytelling in small groups, active role of the teacher as a facilitator, and closing and reflection. This method has provento create a more lively, interactive, and conducive classroom atmosphere for learning. The classroom action research conducted shows that the applicationof the storytelling method can enhance students' speaking skills. In Cycle I, most students began to speak up, although still using simple sentences. After improvements in Cycle II, students showed significant increases in confidence, activity, and ability to develop stories with better and more coherent sentence structures. This improvement is reflected in the observation results, where inCycle I, the average student score was in the "Good" category with an average score of 8.11, while in Cycle II, it increased to "Very Good" with an average score of 94.1. These results indicate that the gradually and purposefullyapplied storytelling method is highly effective in helping students developtheir speaking skills.